Determinants of Micro and Small Enterprise’s Interest to Participate in Self-Declare Halal Certification - Dawam, Khaerud; Laela, Sugiyarti Fatma; Hendrasto, Nur; Rehman, Hafiz Mudassir; Hasan, M. Kabir (Journal of Digital Marketing and Halal Industry, 2023)
The Micro and Small Enterprises (MSEs) market share is expected to increase with the halal certification of their products and services. However, MSEs have limited resources. In response, the Government introduced a self-declare halal certification program in 2022. From the total number of MSEs, which reached 8.7 million units as of March 2023, only about 79 thousand have self-declare halal certificates. Therefore, this study aims to analyze internal and external factors that influence the interest of  MSEs towards halal certification through a self-declare scheme. The study involves 86 MSEs respondents from Bogor, West Java. Using Partially Least Square (PLS) with a second-order approach. The findings reveal that internal factors marginally affect MSE's interest to pursue self-declare halal certification. The three strongest indicators of internal factors are: (1) improving human resource performance, (2) increasing efficiency and financial returns, and (3) awareness of religiosity. Interestingly, external factors do not influence the interest of MSEs to obtain self-declare halal certification, except for government policy, which significantly impact the intention in the first-order test. The main implication of this research is the importance of more substantial government support to help MSEs obtaining halal certification such as socialization, training as well as mentoring Halal Self Declare Certification at an affordable cost.